SENGKETA TANAH ULAYAT MASYARAKAT ADAT DESA SIKIJANG KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI DENGAN PT. RAPP (RIAU ANDALAN PULP AND PAPER) - Herida Nilawati Manurung; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Problems that occur between PT. RAPP (Riau Andalan Pulp and Paper) with the indigenous people of Sikijang Village precisely in Logas Tanah Darat Subdistrict ie Citizen Residents Subdistrict Logas Tanah Darat requested that PT. RAPP (Riau Andalan Pulp and Paper) for an area of 479 Ha in Sikijang Village, Logas District of Tanah Darat. Due to the submission agreed by both parties as stated in the Memorandum of Understanding (MoU), which on August 31, 2000 ago, the 479 hectares of land can be taken by the indigenous people of Sikijang Village after logging, said Head of Logas Tanah Darat, Efrizon Marzuki AP , during negotiations between the two sides at the Kuantan Singingi Forest Service Office Hall. The purpose of writing this thesis, namely: First, To determine what factors that cause the flow of land disputes ulayat between PT. RAPP with Indigenous Peoples of Sikijang Village, Secondly, To know how to settle land disputes of ulayat between PT. RAPP with Indigenous Peoples of Sikijang Village.This type of research can be classified in the type of sociological research is a study of the effectiveness of applicable lawFrom the results of research problems it is clear that the factors that cause the occurrence of land disputes ulayat indigenous Sikijang Village with PT. RAPP, is the non-execution agreement between PT. RAPP with Sikijang Village community, After the agreement ends the promised land of ± 479 Ha is not returned to the community, due to the lack of knowledge of the indigenous peoples thus causing their land to be cultivated or used over the time limit as promised, non-transparent compensation in the execution of grant compensation as compensation for land use, the investor sometimes directly related to the Local Government and even ninik mamak, the community asked to PT. RAPP that the community asked the company to return the land ± 479 Ha and no serious response and settlement made by the company. How to settle land disputes of ulayat between PT. RAPP with indigenous peoples of Sikijang Village was conducted through the mediation stage on September 16, 2014 which resulted from the mediation provided a sum of funds worth Rp. 100 million / year (one hundred million rupiah per year) but not in the form of money but in the form of several programs such as building musollah in several local hamlets. This program has been done since the year 2000 and every year conducted negotiations between the PT. RAPP with Sikijang Village community.Keywords: Settlement of Disputes-Limited Liability Company-Ulayat Land